Penguatan Branding, Digital Marketing, dan Sistem Keuangan pada UMKM Kadai Anugrah Oleh-Oleh Khas Minang - Andi Lolo Gau; Rizki Ramadhan; Pandu Prabowo; Dedi Kurniawan (Fakultas Ekonomi & Bisnis Universitas Jenderal Soedirman, 2025)
Kadai Anugrah is a micro, small, and medium enterprise (MSME) located in Tanah Datar, West Sumatra, that produces various Minangkabau specialty foods such as dendeng balado, kue kering, and keripik as ready-to-eat culinary souvenirs. The business already owns a Business Identification Number (NIB) and halal certification for dry food products, but still faces challenges in marketing expansion, financial recording, and optimization of digital platforms. This community service program aims to strengthen business planning, branding, digital marketing, and simple financial management systems for Kadai Anugrah. The methods used include consultation and mentoring, training on business proposal preparation and SWOT analysis, development and optimization of Instagram and marketplace accounts, improvement of product packaging and brand storytelling, as well as preparation of simple financial report templates and digital cash flow recording. The mentoring results show that Kadai Anugrah has clarified its vision and mission, compiled an initial business proposal, updated and optimized its Instagram profile, created marketplace accounts (Tokopedia and Shopee), improved packaging with bilingual labels and clear serving and storage instructions, and started using a simple digital cash transaction application and Excel-based cash flow templates. In addition, there was an increase in sales performance in the September–early December 2025 period with total revenue reaching IDR 21,650,000, supported by offline sales, PO via WhatsApp and Instagram, and participation in MSME bazaars. The program concludes that integrated mentoring in business planning, branding, digital marketing, and financial management can enhance the readiness of Kadai Anugrah to scale up and expand its market as a typical Minangkabau culinary.